Optimal mechanisms for the control of fiscal deficits - Hans Peter Grüner (European Central Bank (ECB), 2014)
This paper shows that a simple two-stage voting mechanism may implement a constrained optimal state dependent decision about a fiscal deficit. I consider a setup with strategic fiscal deficits à la Tabellini and Alesina (1990). Three groups of voters are informed about the productivity of current public spending. Voters differ in their preferences for public goods and swing voters' preferences may change over time. The current government decides on the current spending mix and it has an incentive to strategically overspend. Under certain conditions, a simple two-stage mechanism in which a deficit requires the approval by a supermajority in parliament implements a constrained optimal decision. When the current majority is small, bargaining between political parties may further increase social welfare. However, when the current majority is large, a supermajority mechanism with bargaining leads to a biased spending mix and reduces welfare whereas the laissez faire mechanism may yield the first best. An appropriately adjusted majority threshold can deal with this problem.
Keywords: D82; H62; 330; constitutional choice; fiscal policy rules; mechanism design